2019
DOI: 10.1159/000489874
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Methylation Status of the Retinoic Acid Receptor-Beta 2 Gene in Breast Cancer Patients: A Case Control Study and Systematic Review

Abstract: Background: We aimed to determine the promoter methylation status of the retinoic acid receptor-beta 2 (RARβ2) gene among breast cancer patients and to review relevant studies in this field in various populations. Methods: We analyzed 400 samples which comprised blood specimens from 102 breast cancer patients, 102 first-degree female relatives of patients, 100 cancer-free females, 48 breast cancer tissues, and 48 adjacent normal breast tissues from the same patients. The RARβ2 methylation status was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…It has been widely demonstrated the diminished of RARB mRNA due to epigenetic alterations in BC. It has been proposed as an epigenetic marker for BC diagnosis [25,43,44]. The role of RARγ has not been extensively studied in the context of BC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely demonstrated the diminished of RARB mRNA due to epigenetic alterations in BC. It has been proposed as an epigenetic marker for BC diagnosis [25,43,44]. The role of RARγ has not been extensively studied in the context of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity and complexity of BrCa, traditional inspection methods, such as immunohistochemical testing, do not identify effective biomarkers to screen and evaluate BrCa ( Network, 2012 ). Researchers examined the mechanisms of the occurrence and development of BrCa from various aspects, such as gene expression disorders ( Cruz et al, 2018 ), copy number variation ( Long et al, 2018 ; Yang et al, 2019 ) and DNA methylation ( Kresovich et al, 2019 ; Yari and Rahimi, 2019 ). Although these studies achieved promising results, they were primarily limited to the transcriptional level, and the post-transcriptional level, such as alternative splicing (AS), was neglected.…”
Section: Introductionmentioning
confidence: 99%
“…14 Yari et al indicated that patients with breast cancer were reported to have higher levels of DNA methylation compared to normal individual. 15 In addition, some researches indicated a marked relationship between the methylation level of gene and susceptibility to breast cancer. 15,16 Moreover, the promoter methylation is closely associated with the gene expression, and some DNA methylation markers have been proven to have prognostic value.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, some researches indicated a marked relationship between the methylation level of gene and susceptibility to breast cancer. 15,16 Moreover, the promoter methylation is closely associated with the gene expression, and some DNA methylation markers have been proven to have prognostic value. 17 In this study, differentially methylated CpG sites were screened using Illumina Infinium Methylation EPIC BeadChip between breast cancer tissues and adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%